1965
DOI: 10.1002/j.2050-0416.1965.tb02068.x
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Phenethyl Alcohol From 14c-Labelled Phenylalanine

Abstract: The two pathways leading to the formation of higher alcohols have been studied by using 14C‐labelled phenylalanine together with an amino acid mixture as substrate, and determining the proportion of phenethyl alcohol derived from the radioactive phenylalanine. Different levels of phenylalanine and total nitrogen have been used to examine the factors regulating the relative importance of the degradative Ehrlich pathway and the synthetic pathway. The results indicate that both pathways must be regarded as potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1967
1967
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Previous reports 30,40,59 have shown that the L‐Phe concentration in the media influences 2‐PE production and that a high L‐Phe concentration is necessary to direct the precursor to the Ehrlich pathway. Also, in the previous experiments in bioreactor, L‐Phe was completely consumed ( supplementary Fig.…”
Section: Bioconversion Experiments At Bioreactor Scalementioning
confidence: 97%
See 1 more Smart Citation
“…Previous reports 30,40,59 have shown that the L‐Phe concentration in the media influences 2‐PE production and that a high L‐Phe concentration is necessary to direct the precursor to the Ehrlich pathway. Also, in the previous experiments in bioreactor, L‐Phe was completely consumed ( supplementary Fig.…”
Section: Bioconversion Experiments At Bioreactor Scalementioning
confidence: 97%
“…However, contrary to what was observed with Y. lipolytica CH 1/5, the productivity values of the shaking flask experiments with S. cerevisiae JM2014 were lower than the ones attained at bioreactor scale. 11 Previous reports 30,40,59 have shown that the L-Phe concentration in the media influences 2-PE production and that a high L-Phe concentration is necessary to direct the precursor to the Ehrlich pathway. Also, in the previous experiments in bioreactor, L-Phe was completely consumed ( supplementary Fig.…”
Section: Strainmentioning
confidence: 99%
“…Then, the derivative aldehyde is reduced to 2-PE by an alcohol dehydrogenase (Etschmann et al, 2002; Figure 2). This is the fastest pathway to produce 2-PE, however cheaper precursors than L-Phe should be used to achieve a more competitive process (ÄYräpää, 1965;Kim T.Y. et al, 2014;Zhang et al, 2014).…”
Section: Strategies For Production Of Aromatic Compoundsmentioning
confidence: 99%
“…In fact, microorganisms are able to produce 2-PE and other alcohols by normal metabolism as the result of amino acid catabolism, but the final concentration of the alcohol is very low (Carlquist et al 2015). The biotechnological approach used to obtain natural 2-PE by bioconversion of L-phenylalanine (L-Phe), as the sole nitrogen source, via the Ehrlich pathway is the best and simple way to enhance the alcohol production (ÄYräpää 1965;Etschmann et al 2002). Through the Ehrlich pathway, L-Phe is firstly converted to phenylpyruvate by transamination, which is then transformed to phenylacetaldehyde by decarboxylation; then, the derivative aldehyde is reduced to 2-PE by dehydrogenation (Carlquist et al 2015;Etschmann et al 2002).…”
Section: Alcoholsmentioning
confidence: 99%
“…As previously described, 2-PE could be produced by bioconversion of L-Phe, as the sole nitrogen source, via the Ehrlich pathway, being this route the best and simple way to enhance the flavor production (ÄYräpää 1965;Etschmann et al 2002). Nevertheless, the Ehrlich pathway uses L-Phe as a substrate to reach the maximum 2-PE concentration and substrates cheaper than L-Phe should be considered to achieve an economic production process (Kim et al 2014a, b;Zhang et al 2014).…”
Section: Alcoholsmentioning
confidence: 99%